A rhetorical balancing act: popular punitivism in the Netherlands - Campbell, Christopher M. (Punishment & society, 2017)
The level of influence public discourse has on policy can vary widely. Research has noted that while it is largely dependent on the topic, frequency, and severity of the message, political rhetoric has the potential to sway public opinion and support. Particularly true for crime policy, rhetoric has historically been a strong factor for many countries such as the United States and England often understood as popular punitivism. However, popular punitivism has not been empirically characterized with specific focus given to political discourse, especially in international context. This paper attempts to capture the scope and relationship between rhetoric, political gain, crime policy, and public response in the Netherlands. Using the context of popular punitivism, we analyze rhetoric from three different political outlets (party platforms, coalition agreements, and statements of the throne) and triangulate the codes with passed policies, voter support, and systemic action. Findings suggest that recent rhetoric often exaggerates observed crime in society, consistent with expectations of popular punitivism perspectives. However, such exaggeration does not necessarily correlate with public support and system response patterns. Implications for discourse theory and popular punitivism are discussed.